Multicultural education: new concepts to be consiudered in the teacher - Reinoso Illescas, Lorena Beatríz
This project is called ?Multicultural Education New concepts to be integrated in teacher´s lesson plans.? It was developed in order to let teachers in Cuenca know about this topic and to encourage them to train and to be better teachers. Before to analyze which concepts should be included in the lesson plans, we have to know what Multicultural Education is. As Nieto mentions, it is a school reform where students learn about pluralism and cultural differences in a school (qtd. In Multicultural Education 110). Nowadays the government is working, in order to integrate multicultural concepts in the educational system. Government has made reforms in the national constitution, and in the Educational law. All these efforts have helped to start a process of an improvement in Education. A teacher must be able to develop the lesson plan with content of different cultures, the lesson has to encourage students to reduce their negative racial attitudes, to increase social justice, and to develop a critical criteria among similarities and differences of cultures. This work includes opinions of English Native Speakers about multicultural education. Besides, a group of high school students were surveyed in order to know how much they are aware of cultural differences among their classmates. Finally, two lesson plans are proposed, which include several activities with multicultural content.